Analysis of the genetic diversity in Metopolophium dirhodum (Walker) (Hemiptera, Aphididae) by RAPD markers - Lopes-da-Silva,Marcelo (2007)
The emergence of host-races within aphids may constitute an obstacle to pest management by means of plant resistance. There are examples of host-races within cereals aphids, but their occurrence in Rose Grain Aphid, Metopolophium dirhodum (Walker, 1849), has not been reported yet. In this work, RAPD markers were used to assess effects of the hosts and geographic distance on the genetic diversity of M. dirhodum lineages. Twenty-three clones were collected on oats and wheat in twelve localitites of southern Brazil. From twenty-seven primers tested, only four primers showed polymorphisms. Fourteen different genotypes were revealed by cluster analysis. Five genotypes were collected only on wheat; seven only on oats and two were collected in both hosts. Genetic and geographical distances among all clonal lineages were not correlated. Analysis of molecular variance showed that some molecular markers are not randomly distributed among clonal lineages collected on oats and on wheat. These results suggest the existence of host-races within M. dirhodum, which should be further investigated using a combination of ecological and genetic data.